Diversity Census of Fecal Microbiome in Horses - Seul Lee; Minseok Kim (The Korean Society of Animal Reproduction and Biotechnology, 2019)
This study was conducted to analyze the diversity census of fecal microbiome in horses using meta-analysis of equine 16S rRNA gene sequences that are available in the Ribosomal Database Project (RDP; Release 11, Update 5). The search terms used were "horse feces (or faeces)" and "equine feces (or faeces)". A total of 842 sequences of equine feces origin were retrieved from the RDP database, where 744 sequences were assigned to 10 phyla placed within Domain Bacteria. Firmicutes (n = 391) and Bacteroidetes (n = 203) were the first and the second dominant phyla, respectively, followed by Verrucomicrobia (n = 58), Proteobacteria (n = 30) and Fibrobacteres (n = 24). Clostridia (n = 319) was the first dominant class placed within Bacteroidetes while Bacteroidia (n = 174) was the second dominant class placed within Bacteroidetes. The remaining 98 sequences were assigned to phylum Euryarchaeota placed within Domain Archaea, where 74 sequences were assigned to class Methanomicrobia. The current results will improve understanding of the diversity of fecal microbiome in horses and may be used to further analyze equine fecal microbiome in future studies.